Factors influencing obstetric brachial plexus injuries. (7th June 2011) - Rao, G Gangadhara; Hart, D; Ramalingam, K
Abstract : Purpose of study: To study risk factors associated with obstetric brachial plexus injuries (OBPI) and to study outcomes of OBPI. Methodology: Retrospective audit study. All neonates with OBPI that were diagnosed in a tertiary maternity and neonatal unit over a 6 year period were identified and data about associated factors was collected from electronic health records and patients' case notes. Results: A total of 68 patients were identified between 2004 and 2009 averaging 2 per 1000 live births. 55% of mothers had body mass index (BMI) more than 25. In the general obstetric population, 40.5% of mothers had BMI >25 at booking. 85% of neonates with OBPI were over 4.5 kg. 51% of babies had shoulder dystocia. 95% of OBPIs were unilateral. 15% of OBPIs had associated injuries such as clavicle and humerus fractures. 7% of babies with OBPI were referred to a tertiary nerve injury unit. 69% of OBPIs resolved completely at 3 months of age, 22% between 3 and 12 months and 4% resolved after 12 months. 4% of the babies with OBPI needed ongoing follow-up after 12 months of age. Conclusion: OBPI is more likely to be associated when maternal BMI is more than 25 and birth weight of infants more than 4.5 kg. Complete resolution of OBPI within 3 months of age was observed in more than 2rd/3rd of the patients. The risk of sustaining OBPI should be individualised depending on antenatal risk factors. Most injuries resolve completely.